Rethinking friendship : hidden solidarities today (PRINCETON : PRINCETON UNIV Press, 2006)
"Rethinking Friendship not only describes the varied nature of personal relationships today, but also locates friendship in contemporary debates about individualization and the supposed "collapse of community." Exploring friendships with partners and family as well as "friends," the book reveals ways in which friends and friendlike ties are an important and unacknowledged source of social glue." "Combining scholarly depth and rich description, this book will appeal to all those interested in informal social relationships, including students of methodology and policymakers."--Jacket.
The fragmentation of social life? -- Capturing personal communities -- The nature of friendship -- Patterns of friend-making -- Friends and family : the case for suffusion -- Personal communities today -- Micro-social worlds in the making -- Hidden solidarities revealed -- Appendix : how we carried out our study.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Friendship; Communities; Community life; Friends; Amitié.; Communauté.; PSYCHOLOGY -- Social Psychology; Community life; Communities; Friendship; Vriendschap; Sociale relaties